Determinants of herding behaviour among individual investors of Pakistan stock exchange - Sabir, Saeed Ahmad (2020)
The most crucial role for investors is to make rational investment decisions in which it depends on their investment behaviour. Investment behaviour of investors plays a vital role in the performance of an investment. Normally, investors are unable to gather relevant information which leads them to behavioural biases and cognitive errors. Ultimately, investors might make a wrong investment decision that could become the cause of failure to the investment. Numerous cognitive factors have influenced investors' behaviour during the decision-making process, and lead them to herd the acts of others. This herding behaviour is irrational as it becomes the cause of asset mispricing in the stock market. To address these issues, the current study highlights the role of investors' cognitive profile, past investment experience and information availability on herding behaviour. This study also examines the moderating role of financial literacy on the relationship between the cognitive factors, past investment experience, information availability and herding behaviour. The data of the study was gathered from individual investors in the Pakistan Stock Exchange by using random sampling technique. Using the survey questionnaire, 540 questionnaires were distributed which yielded a 56.29% response rate. Partial Least Square (PLS)-Structural Equation Modeling (SEM) was used to analyse the data. It was concluded that illusion of control, self-attribution, overconfidence and past investment experience have a significant positive influence on the herding behaviour among individual investors in the Pakistan Stock Exchange. Meanwhile, information availability mitigated the herding behaviour of individual investors in Pakistan Stock Exchange. Besides, financial literacy has moderating role on the relationship of illusion of control and past investment experience with herding behaviour. This study could be beneficial for Pakistan Stock Exchange (PSX), Security and Exchange Commission of Pakistan (SECP) and the Pakistani government in formulating strategies to mitigate the herding behaviour among individual investors by enhancing their financial literacy.